Functional screening of somatic mutant events in extranodal natural killer/T-cell lymphoma with adrenal involvement - Zhang, Luxin; Gao, Haifeng; Ma, Shuang; Fan, Xiaoming; Guo, Huahang; Sun, Man; Wen, Shuang; Liu, Tianqing; Yu, Guanghai; Yuan, Xiaoying; Sun, Xiuhua; Fan, Bo (Frontiers in Immunology, 2025)
BackgroundExtranodal natural killer/T-cell lymphoma (ENKTL) involving the adrenal glands is extremely rare, and only a few cases have been reported. However, the genetic alterations, clinicopathological features and prognosis of these patients have not yet been fully elucidated.MethodsProfiling of tumor mutations in ENKTL patients with adrenal involvement was conducted by whole-genome sequencing, and the predisposing genes and driver mutation gene variants were verified through Sanger sequencing. Immunohistochemical analysis of markers for the diagnosis and tumor microenvironment competent were performed to identify histopathological features. In addition, we searched the Surveillance, Epidemiology, and End Results (SEER), PubMed, Embase, and Scopus databases to perform a population-based study to compare the prognosis between adrenocortical carcinoma (ACC) patients and adrenal ENKTL patients using Kaplan–Meier survival curves and log-rank tests and analyzed the prognostic factors affecting the overall survival (OS) of adrenal ENKTL patients via univariate and multivariate Cox regression analyses.ResultsWe screened 15892 somatic single-nucleotide variants (SNVs), 364 somatic insertions and deletions (INDELs), and four driver mutation genes, namely, TET2, STAT3, FAS, and TP53. In addition, immunohistochemical analysis revealed that tumor cells were positive for CD3, CD43, CD56, TIA1, granzyme B, CD2, CD4, and CD7. The immunohistochemistry for detecting components of the tumor microenvironment reveled the infiltration of tumor-associated macrophages (CD68, CD163) and tumor-associated fibroblasts (vimentin, SMA) in the tumor sample. According to our population-based analysis, Kaplan–Meier survival curves revealed that ENKTL patients with adrenal involvement had a significantly poorer prognosis than did patients with ACC (p<0.001), and chemotherapy was a significant prognostic factor for OS in ENKTL patients with adrenal involvement according to Cox multivariate analysis (hazard ratio = 0.318; p=0.027).ConclusionsThe metastasis of ENKTL to the adrenal gland may be due to gene mutations caused by genetic variations, which may provide new therapeutic targets for this disease. The prognosis of adrenal ENKTL patients is markedly worse than that of ACC patients, and chemotherapy may serve as an independent factor of OS in adrenal ENKTL patients. However, our findings still need to be validated in additional studies.